Transcriptome analysis of honey bee larvae following neonicotinoid exposure - Snart, Charles J.P. (2011)
The current decline of the European Honey Bee (Apis Mellifera) has been linked to the increasing use of neonicotinoid pesticides within agriculture. Whilst the toxicity of these pesticides to Apis has long been established, the possibility of low dosages inducing molecular stress has not yet been fully explored. Of particular interest is the action of these nicotine derivatives on the nicotinic acetylcholine receptor, and its association with the DNA methyltransferase family (Dnmts).